Post-Traumatic Stress Disorder: A Review of Current Causes and Treatment - A‏mal tawfiq al arooj et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Post-Traumatic Stress Disorder (PTSD) is a severe and often chronic mental health condition that arises following exposure to traumatic events. It affects millions worldwide, leading to significant emotional, physical, and social impairments. This review provides an overview of current understanding regarding the causes of PTSD, including risk factors, biological mechanisms, and psychological influences, as well as the treatments available, focusing on both established and emerging therapeutic approaches. Keywords: Post-Traumatic Stress Disorder, psychotherapy, medication. Received Date: September 13, 2024 Accepted Date: October 11, 2024 Published Date: November 11, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/199 DOI: https://doi.org/10.5281/zenodo.14082271